Enablers of open innovation in software development micro-organization - Mateusz Trzeciak; Łukasz Daniel Sienkiewicz; Emil Bukłaha (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
The implementation of the open innovation (OI) model is associated with a significant organizational change within the existing processes, business models, and prevailing customs. This change takes appropriate measures to prepare for and conduct an effective implementation process. Only a small number of research concerns software development micro-organizations using the OI model. Therefore, this article focuses on defining and systematizing the activities supporting the implementation of OI, which are initiated depending on the implementation process and the organizational level at which a given process is implemented. The research was carried out based on a case study in the Sandstream Development Sp. z o. o. (SSD) organization by analyzing the approach to the implementation of the Sandtime.io project. As a result of the undertaken research effort, the assumed research goal and a theoretical model of implementing open innovations in software development micro-organizations were developed. In addition, the importance of preparing the foundation for the OI model was also emphasized through the recommendations for managers regarding the implementation of individual implementation activities.
Keywords: 650; capacity for internal innovation; competitive advantage; culture and values; open innovation; project management; semi-open-source product